Computational and Optimization Design in Geometric Acoustics. Issue 1 (March 2014) - Bassuet, Alban; Rife, Dave; Dellatorre, Luca
The use of 3D computer modeling tools through the 90s has revolutionized the practice of architecture. Coupled with new fabrication processes, these have introduced new territories for architectural design. Such techniques are also available to acoustic designers for the shaping of spaces. With 3D modeling programs such as Rhino3D and Grasshopper incorporating NURBS, geometries can be easily adjusted to meet both aesthetic and functional objectives. Control points of NURBS elements give access to the parameterization of geometries which subsequently can be assigned variables and open the way to computational design optimization. Through several performing arts project examples, this paper gives an overview of processes used today by acousticians to refine designs either through iterative design, auralization, optimization algorithms and real-time computer modeling. Contextualized with design practices from different periods of history, the paper discusses the relevance of computational and optimization tools in the design process of shaping rooms, walls and reflectors and how these methods can support creativity, accelerate solution finding, and interface with complex architectural ideas.